El Reglamento comunitario y la Ley Concursal en el nuevo Derecho internacional privado de la insolvencia (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The EC Insolvency Regulation 2001 became effective in May 2002. The Spanish Insolvency Act 2003 will enter into force in September 2004. After describing the current status of insolvency in Private International Law, the paper analyses the scope of application of both the Regulation and the Act and their relationship. The Regulation applies only to intra-community insolvency proceedings (i.e., when the centre of the debtor’s main interests is located within the territory of a Member State). The paper attempts to clarify the scope of the Regulation in various aspects, such as: international jurisdiction, choice of law, recognition of proceedings, interrelationship of parallel proceedings and the creditor’s right to lodge claims and to receive information. Once the scope of the EC Insolvency Regulation has been clarified, the scope of the Spanish Insolvency Act can then be ascertained.